PENGARUH BRAND AWARENESS DAN PERCEIVED QUALITY TERHADAP COSTOMER SATISFACTION YANG DIMEDIASI OLEH BRAND EQUITY PADA PENGGUNA SMARTPHONE - Muhammad Zaiyad Rizqullah; Sulaiman Sulaiman (Departemen Manajemen, 2021)
This study aims to examine the influence of Band Awareness and Perceived Quality on Customer Satisfaction mediated by Brand Equity on smartphone users. The sample used in this study was 394 students of Syiah Kuala University using probability sampling techniques. Then, the data collection used in this study was study uses data collection equipment, namely a questionnaire (-questionnaire). This study uses Structural Equation Modeling (SEM) as a method of analysis to determine the effect of the variables involved in mediation testing in this study. The results of SEM analysis shows that Perceived Quality and Brand Awareness have a positive effect on Brand Equity. Brand Equity, Brand Awareness, and Perceived Quality have a positive effect on Customer Satisfaction. Brand Equity acts as a mediator of the relationship between perceived quality and customer satisfaction as well as the relationship between brand awareness and customer satisfaction